تحليل الأخطاء الأسلوبية في التعبير التحريري العربي لدى طلاب الشهادة الثانوية الماليزية - Muhammad Hakim Rosly (Kulliyah Ma'arif al-Why wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2008)
This study attempts to investigate stylistic errors in Arabic essays of students sitting for the Sijil Pelajaran Malaysia (Malaysian Certificate of Education), as well as other language-related problems. This study will analyze stylistic errors and its features by extensively explaining why they occur in the students' writings. Therefore, special attention will be given to theories related to the term “stylistic error” as well as views related to “style” with several principles of developing style and its elements, especially in the scope of teaching Arabic as a second language. This study adopts descriptive and analytical methods to analyze causes behind these problems by studying questionnaires and samples of students' essays. The study has identified some of the main causes that lead to students' problems and weaknessess in writing Arabic essays namely: 1. Lack of reading in Arabic, 2. Lack of writing drills, 3. The process of essay writing is a difficult and complicated in nature. Some of the causes of stylistic errors are: 1. Unnecessary word-by-word translation, 2. The inability to use appropriate words and phrases in the right context, 3. The inability to use appropriate Arabic connectors, 4. Repeating the same word or pronoun unnecessarily, 5. The imbalance of using Arabic noun sentence and Arabic verb sentence. In order to overcome stylistic errors, the researcher suggests that the characteristics of the Arabic Language should be mastered in order to improve their style of writing. Additionally, stylistic errors could be reduced by using writing drills repeatedly, as suggested in this study.